National medical service
1943-10-20 1943 1940s 15 pages PRIVATE & CONFIDENTIAL. Jt.S.I.C.&.W.C.&.F.C.1/1. 20th October, 1943 TRADES UNION CONGRESS. NATIONAL MEDICAL SERVICE. 1. For years reforms and extension of the Medical Services of Great Britain has been proposed from many quarters. It was clear that the present services were too limited, too restricted, even as far as individual personal treatment was concerned, administratively too disjointed, socially unfair and maldistributed, with permissive health legislation providing uneven local administration, and with lack of desirable co-ordination centrally. The whole present Medical system was chaotic. Though the Ministry of Health was regarded as the main administrative health centre nationally, with supervision of and sometimes control over, social medical services, such as public health, general sanitation, water supply, housing, local authority hospitals, tuberculosis, maternity and child welfare, cancer, venereal disease, and with more personal individual services, such as are covered by National Health Insurance administration, there were obviously many gaps in the sphere of a co-ordinated National Health Service. Industrial Health, Factory Act administration and Workmen's Compensation affairs were relegated to the Home Office (and now are partly divided between the Home Office and the Ministry of Labour). Medical research, via the Medical Research Council and its subsidiary, the Industrial Health Research Board, remained under the Privy Council. The question of seamen's health protection and limited treatment facilities and Port Welfare remains under the Board of Trade. The School Medical Service is under the Board of Education and Mental health and its administration is delegated rightly to the Board of Control by the Ministry of Health. The medical side of the three Fighting Services remains separate, and also does the Medical Service to Postal Employees under the Post Office. The Assistance Board still runs a limited Medical Service. The Treasury exercises medical supervision over Government Departmental medical standards on recruitment through its own appointed Treasury medical referees and those of the Civil Service Commissioners. The recently appointed Mining Medical Services are being run by the Ministry of Fuel and Power. Voluntary agencies run Medical Services and Institutions, such as the Voluntary Hospitals, private clinics, private nursing homes, etc., without any statutory right of inspection or investigation. 2. Medical Education, one of the most important aspects of Medical Services and Administration, is left in the hands of the General Medical Council, founded by the Medical Act of 1850 and with untouchable powers within its statutory sphere. Nearly a century old it has remained practically unreformed with its accredited powers of medical registration (through which it governs autocratically medical behaviour and professional ethics without appeal, medical education by recognition of medical teaching schools) and the authorisation of the British Pharmacopoeia by which drugs and drug preparation are standardised. Though originally intended for the protection of the public so that the trained qualified medical practitioner could readily be distinguished from "the untrained", it is practically a purely medical (professional) corporation, with only 6 (out of 36) elected medical representatives and one lay Government nominee. The vitally important point here is that Medical Education, with its great importance on social well-being and civil health is in the hands of a very conservative profession and not in the hands of the State or communal democracy. It is unilateral control, worse than dual control. To ensure desirable change, this body 292/847/2/113